Correction: Red phosphorescent binuclear Pt(ii) complexes incorporating bis(diphenylphorothioyl)amide ligands: synthesis, photophysical properties and application in solution processable OLEDs. Issue 38 (24th September 2021) - Suo, Xia; Nie, Chuanli; Liu, Weiqiang; Zhang, Yuzhen; Shen, Yunjun; Bian, Hedong; Cheng, Gang
Abstract : Correction for 'Red phosphorescent binuclear Pt(ii ) complexes incorporating bis(diphenylphorothioyl)amide ligands: synthesis, photophysical properties and application in solution processable OLEDs' by Xia Suo et al., J. Mater. Chem. C, 2021, 9, 9505–9514, DOI: ; 10.1039/D1TC02087K .